Pendugaan Umur Simpan Rendang Telur yang Dikemas Plastik High Density Polyetilen (HDPE) dan Aluminium Foil dengan Teknik Pengemasan Berbeda Menggunakan Metode Akselerasi - Raswen Efendi; Dewi Fortuna Ayu; Nadya Nofaren (Agricultural Faculty, 2021)
The purpose of this research is to estimate the shelf life of egg rendang that is packed with High Density Polyetilen (HDPE) plastic, aluminium foil, and vacuum aluminium foil. Estimation of shelf life using the acceleration method by storing the egg rendang for 30 days at three different temperatures, i.e, 30°C, 35°C, and 40°C. The parameters observed during the storage process were sensory assessments of rancidity and thiobarbituric acid (TBA) values of egg rendang. Data were analyzed using linear regression and the equations obtained were used to calculate the shelf life of egg rendang at normal temperature, which is 27°C. The egg rendang stored using vacuum aluminium foil packaging have a longer shelf life compared to HDPE packaging and non vacuum aluminum foil. The egg rendang shelf life packed with aluminium foil vacuum based on rancidity sensory test was 100 days, with the regression equation y =-7241,9x+20,317, an activation energy (Ea) of 14.382,4 kal.mol-1, and the value of quality degradation (k) was 0.021 quality unit per day. The egg rendang shelf life packed with aluminium foil vacuum based on the TBA value was 99.50 days, with the regression equation y =-6995,3x+18,577, the activation energy (Ea) of 13.892.7 kal.mol-1, and the value of quality degradation (k) was 0.008 quality unit per day.